Resurgence of common respiratory viruses and mycoplasma pneumoniae after ending the zero-COVID policy in Shanghai - Pengcheng Liu; Menghua Xu; Lijuan Lu; Xunhua Zhu; Ran Jia; Niuniu Dong; Liyun Su; Jin Xu (Scientific Reports)
Abstract China has adhered to policies of zero-COVID for almost three years since the outbreak of COVID-19, which has remarkably affected the circulation of respiratory pathogens. However, China has begun to end the zero-COVID policies in late 2022. Here, we reported a resurgence of common respiratory viruses and Mycoplasma pneumoniae with unique epidemiological characteristics among children after ending the zero-COVID policy in Shanghai, China, 2023. Children hospitalized with acute respiratory tract infections were enrolled from January 2022 to December 2023. Nine common respiratory viruses and 2 atypical bacteria were detected in respiratory specimens from the enrolled patients using a multiplex PCR-based assay. The data were analyzed and compared between the periods before (2022) and after (2023) ending the zero-COVID policies. A total of 8550 patients were enrolled, including 6170 patients in 2023 and 2380 patients in 2022. Rhinovirus (14.2%) was the dominant pathogen in 2022, however, Mycoplasma pneumoniae (38.8%) was the dominant pathogen in 2023. Compared with 2022, the detection rates of pathogens were significantly increased in 2023 (72.9% vs. 41.8%, p < 0.001). An out‐of-season epidemic of respiratory syncytial virus was observed during the spring and summer of 2023. The median age of children infected with respiratory viruses in 2023 was significantly greater than that in 2022. Besides, mixed infections were more frequent in 2023 (23.8% vs. 28.9%, p < 0.001). China is now facing multiple respiratory pathogen epidemics with changing seasonality, altered age distribution, and increasing mixed infection rates among children in 2023. Our finding highlights the need for public health interventions to prepare for the respiratory pathogen outbreaks in the post-COVID-19 era.